Economy, punishment and imprisonment - Hale, Chris (Contemporary crises, 1989)
Recent trends in sentencing in England and Wales are discussed and related to the debate concerning the relationship between unemployment and imprisonment. The shift towards a more punitive justice system are traced to the abandonment of full employment economic policies in the mid 1970s.